Anthelmintic Activity of Ethanolic Extract of Syzygium samarangense (Blume) Merril & Perry (Dhaka University Journal of Pharmaceutical Sciences, 2016)
Abstract not availableDhaka Univ. J. Pharm. Sci. 15(1): 109-111, 2016 (June)